Konstnärligt intrång - Hellqvist, Stina (2008)
"Claiming the right to space" is an argument frequently used by street artists for justifying illegal art in the public space. The public city space as a room of democracy and right to free speech is by some people considered threatened by commercial interests, and street art has become a way to demonstrate disapproval towards this. Street art is illegal and often anonymously performed in our cities. It developed in the late 1970s from the urban graffiti scene in America, and has therefore a lot in common with the graffiti movement. While there are similarities between the two, there are also fundamental differences. In this essay only street art is therefore considered.